Reading in Phenomenology: Heidegger’s Approach to Religious Experience in St. Paul and St. Augustine - O’Rourke, Jonathan (Open theology, 2020)
The importance of religious figures in Heidegger’s early development has long been understood. Beginning especially in the WS-1920 , with the Phenomenology of Religious Life lectures, figures such as Paul and Augustine played essential roles in his early attempt to move beyond the legacy of Cartesian thought. Despite appearing to secularize these accounts, Heidegger nonetheless implies that it is because of their religiosity, and not in spite of it, that they are of phenomenological interest. For this reason, the exact status of religious descriptions in his phenomenology has been a source of contention. My argument in this paper, is that this status is best understood by turning to Heidegger’s early approach to phenomenological reading. This approach, I argue, is grounded in a performative model of language, exemplified in Destruction [ Destruktion ], and defines the limits within which he can engage with the religious character of historical texts.